Conditional Influence of Media: Media Credibility and Opinion Formation - Bushra H. Rahman (Journal of Political Studies, 2014)
This study explores the relationship between media usage, credibility, and political opinion formation among educated Pakistani youth. The relationship is studied under the premise that as trust plays an important role in many all areas of social life, it will influence the opinion of the audience. Following the same logic the study proposed that trust in media would facilitate media’s effectiveness in formation of opinion. Findings show that the in heavy viewing of TV news channels does not have any relationship with the way people perceive the credibility of the channels and it also does not affect the opinion making process, the perceived credibility of the media is a more important factor in the formation of political opinion.